SOCIAL MEDIA REVIEW ARTICLE: ANALYSIS OF CHANGES IN COMMUNITY BEHAVIOR TOWARDS THE USE OF SOCIAL MEDIA AND THE IMPACT OF SECURITY RISK THREATS: English - Abdul, Najib (PT. Jurnal Center Indonesia Publisher, 2026)
Social media and security are a combination of two inseparable elements between social media and security, the security context referred to here is the security of social media users in communicating and resilience to potential risks due to the use of social media. Through social media platforms, such as Instagram, Facebook, Tik Tok, and Finteres which provide various features to facilitate interaction between social media users. Changes in today's information technology have brought major changes to all levels of society. With the birth of social media, behavioral patterns have shifted quite significantly, both in terms of ethics, culture and social norms. The research method used is quantitative descriptive through a descriptive analysis process. This study explains the behavior of new media usage activities by the Digital Community / Gen which includes motivation, habits or behavior, and security of social media access. Security can also be found in the data we use in the process of using social media, because when using communication access on a digital platform, there is a direct risk that all data directly related to the communication process can be known by other parties.